Binding Success and Failure: Evidence for the Spontaneous Integration of Perceptual Features and Object Evaluations - Hommel, Bernhard; Keizer, Andre (Frontiers in Psychology, 2012)
Humans represent perceptual events in a distributed, feature-specific fashion, which calls for some sort of feature integration. It has been suggested that processing an event leads to the creation of a temporary binding of the corresponding feature codes – an object file. Here we show that object files do not only comprise of perceptual feature codes but also include codes that reflect evaluations of the perceptual event.